2022
DOI: 10.1002/agm2.12214
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and oral anticoagulant prescription in adults with atrial fibrillation: A systematic review

Abstract: Atrial fibrillation (AF) is the most diagnosed cardiac arrhythmia in clinical practice, with increasing incidence and prevalence among older people. 1,2 Aging is a major risk factor, with 70% of patients with AF between the ages of 65 and 85 years old. [3][4][5][6] Particularly with the aging population, the risk of AF continues to rise. The global burden of AF is expected to double from 125 million to 434 million over the next two generations, it is an increasingly important public health issue. 7 This has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Therefore, physicians are reluctant to administer anticoagulation therapy to frail older patients. A recent systematic review of frailty and anticoagulation therapy demonstrated that frailty has led to a reluctance to prescribe anticoagulants 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, physicians are reluctant to administer anticoagulation therapy to frail older patients. A recent systematic review of frailty and anticoagulation therapy demonstrated that frailty has led to a reluctance to prescribe anticoagulants 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In daily practice, physicians will implicitly weigh multiple factors when deciding on the optimal anticoagulant treatment that is very difficult to adjust for in observational studies. 5,11 Monitoring through international normalized ratio (INR) testing allows for intervening at an early stage by titrating the VKA dose to the most optimal range, which may be beneficial in older patients living with frailty given their larger volatility in anticoagulant status. As a result, it is uncertain whether the superiority of NOACs over VKAs in patients with AF observed also holds for frail patients with AF, and the question whether these patients with AF taking VKA should be switched to an NOAC remains heavily debated.…”
Section: Joosten Et Almentioning
confidence: 99%